Dyslipidemia among patients with type 2 diabetes in Jordan: Prevalence, pattern, and associated factors - Hyassat, Dana; Al-Saeksaek, Saba; Naji, Duha; Mahasneh, Awn; Khader, Yousef; Abujbara, Mousa; El-Khateeb, Mohammad; Ajlouni, Kamel (Frontiers in Public Health, 2022)
Objectives: To determine the prevalence and patterns of dyslipidemia and its associated risk factors among patients with type 2 diabetes attending the National Center for Diabetes, Endocrinology, and Genetics (NCDEG). Methods: A cross-sectional study was conducted at the NCDEG in Amman, Jordan. A total of 971 patients with type 2 diabetes were included during the period September- December 2021. The socio-demographic data were collected through face-to-face interview questionnaire and anthropometric and clinical data were abstracted from medical records. The last three readings of lipid profile and HbA1C were abstracted from the medical records. Results: The overall prevalence of dyslipidemia among type 2 diabetic patients was 95.4%. The most common type of dyslipidemia was combined dyslipidemia (37.1%), with high triglycerides and low HDL-c (19.0%) being the most frequent type. Factors associated with hypercholesterolemia were diabetes duration ≤10 years, poor compliance to a statin, and HbA1c level (7-8%) (P-values: 0.008, 0.001, 0.021, respectively). Moreover, smoking and poor compliance with statin therapy were associated with high LDL-c level (P-values: 0.046 and 0.001, respectively). The presence of hypertension, high waist circumference, HbA1c level >8%, and diabetes duration ≤10 years were all associated with high triglyceride level (P-values: 0.008, 0.016, 0.011, and 0.018, respectively). Hypertension and HbA1c level >8% were associated with low HDL-c level (P-values: 0.010 and 0.011, respectively). Conclusion: The combination of high triglyceride and low HDL-c is the commonest lipid abnormality detected in patients with type 2 diabetes. An educational program that emphasizes the importance of adherence to a healthy lifestyle is strongly recommended. Further studies are needed to capture a wide range of factors that might influence dyslipidemia and glycemic control.